A study of the effectiveness of SIRIM QAS International Sdn. Bhd. on customer service programs - Kamarudzaman, Ahmad Firdaus (2006)
This study is design to investigate the effectiveness of customer service programs at SIRIM QAS International. It focuses on the customer service programs done, level of satisfaction of customers and preferences towards the programs. From this study the researchers intend to discover what the turning point is and help SIRIM in improving the customer service programs that already exist. The findings of this study will hopefully provide further insight in identifying and understand the particular consumer service programs. Such information will definitely assist the management of SIRIM QAS International in further providing and maintaining service quality.